Children with pertussis inform the investigation of other pertussis cases among contacts - Rodrigues Laura C; Magalhães Vera S; Baptista Paulo N (BMC, 2007)
Abstract Background The number of reported pertussis has increased in the last two decades. However, many cases of pertussis may be underreported or not diagnosed. The World Health Organization estimates that pertussis causes 200.000 - 400.000 deaths each year, most deaths are in infants and in developing countries. Infants with pertussis can indicate an undetected source cases in the community. Methods At a University Hospital in Brazil individuals that had frequent contacts with a child with confirmed pertussis (the index case) and had recent history of cough were enrolled into the study. Nasopharyngeal swabs were collected from every contact that had cough within the last 21 days. Cases confirmation followed the guidelines of the Center for Disease Control and Prevention - Atlanta, U.S.A. Results Pertussis diagnosis was confirmed in 51 children, (considered the index cases). Among the index cases, 72.5% (37/51) were under 6 months of age; culture for Bordetella pertussis was positive in 78.4% (40/51). Pertussis was confirmed in 39% (107/276) of the contacts of 51 index cases. Among these contacts identified as a pertussis case, 40.2% (43/107) were between 6 months and 111/2 years of age and 59.8% (64/107) were older than 111/2 years of age. Pertussis was confirmed by culture in 11.2% (12/107) of them and by epidemiologic linkage in 88.8% (95/107). Each index case allowed identifying two new cases of pertussis. Conclusion Public health authorities should consider implementing early recognition of pertussis index cases and searching for pertussis cases among the contacts. Treatment of the cases and prophylaxis of the contacts is fundamental to control outbreaks in the community.